Pendampingan Optimalisasi Produksi pada Industri Rumah Tangga â€œKerupuk Nasi Bersamaâ€ di Desa Pematang Baih Kabupaten Rokan Hulu - Daruwati, Ika; Lesmana, Andi; Anwar, Saiful (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service aims to increase the quality and quantity of rice cracker production in household households through the application of appropriate technology. The method of implementing this service used training and mentoring. The partners of this activity were members of the â€œKerupuk Nasi Bersamaâ€ Home Industry in Pematang Baih Village, Rokan Hulu Regency, Riau Province. The results of this service showed that IRT partners had the ability to operate automatic cracker cutting equipment technology and dough mixer machines so that they could increase the quality and quantity of rice cracker production. This Appropriate Technology makes it easier for housewives to repair and increase product quality and quantity.